Integration of data analysis and data acquisition software in prototype photo-CELIV set-up - Meyyappan, Ramasamy (2019)
The aim of this project is to create function program using the LabVIEW platform to analyze optical electrical measurement data and extracting the set of essential parameters which are useful for assessing device performance. The measurement comprises of the current-voltage, charge extraction by linearly increasing voltage (CELIV) with light excitation (Photo-CELIV). The program can distinguish various file formats, process the data and focus on the parameters which significantly reduces the time taken on the actual processing of data. The software is able ot utilize the measured data with mathematical functions in order to extract and calculate the necessary parameters. The end product is ensured to make it user friendly and for further advancements on handling larger data.